THE INTERTEXTUALITY OF ASSERTIVE ACTS PERFORMED BY OPHELIA IN HAMLET DRAMA AND OPHELIA MOVIE - Chory Afri Andari; Muhammad Zainal Muttaqien (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This study aimed at describing the intertextuality of assertive speech acts performed by Ophelia, the main character of the drama entitled The Tragedy of Hamlet: Prince of Denmark and the movie entitled Ophelia. There were three theories underlying this research, namely assertive speech act theory from Searle (1979), intertextuality theory from Genette (1997), and the collaborative oriented theory from Maltz & Bolker (1982). This research employed descriptive-qualitative method since the data are in the forms of texts and the objective was describing phenomena. The main instrument of this research was the researcher themselves with referential sources, data sheets, and word processor as some of the supporting instruments. The data were taken from the script of the drama and the movie and collected by documentation and validated through investigator triangulation by involving an expert in linguistics. The collected data were then analyzed by the process of reduction, data display, and conclusion drawing as well as verification. The results showed that informing act, implicit intertextuality, and criticizing other people are the most frequent categories appearing in the dialogues.